Chapter Le coste dei Nebrodi tra mosaico paesaggistico, beni culturali e criticità complesse. Visioni e Scenari Strategici progettuali nel paradigma della sostenibiltà - Pidalà, Andrea Marçel (Proceedings e report, 2020)
The coastline that delimits Nebrodi geographical area, includes beaches, coastlines and areas urbanized along a border section of about 104 km with 15 urban centers. The coastline is divided in 3 sections: beaches; dunes; waterfronts. The coastline defines a territory complex, where natural and human activities intertwine shaping the places. Relationship between man and nature determines environmental criticizes increasing, requiring strategic intervention with a holistic-integrated vision. Progressive urbanization has produced stiffening of coastline and questioning of ecological cycles.